Comovement in the Chinese CSI 300 Index - Wang, Bohan (Simen Owen Academic Proceedings Series, 2025)
This study examines whether comovement exists in the Chinese stock market by investigating the relationship between individual stock returns and the CSI 300 Index. Using both univariate and bivariate regression analyses, we test the changes in beta coefficients and R-squared values when a stock is added to or removed from the CSI 300 Index. The empirical results indicate that the overall change in these parameters is statistically insignificant. To further explore this phenomenon, we analyze the potential influence of index arbitrageurs on comovement. The findings remain robust even after accounting for the mean reversion of beta. Therefore, the results provide strong evidence that comovement in the Chinese stock market is statistically significant.